(untitled) (Research, Society and Development, 2021)
Introduction: The monitoring of nephrotoxic antimicrobial use and the identification of probable problems related to their use in patients with renal risk factors is of the utmost importance, mainly regarding the safety and protection of patients’ health. The present study aimed to analyze the use of restricted-use antimicrobials in hospitalized patients with renal dysfunction. Methods: This is a cross-sectional retrospective study carried out from January to March 2015, which included the following variables: age, gender, comorbidities, type of kidney disease, hospitalization unit, and antimicrobial sused, classified according to the ATC (Anatomical Therapeutic Chemical) methodology. Results and Discussion: records of renal dysfunction were found in 113 monitored patients, most of which were males, with CKD, and aged between 60 and 89 years. The most commonly prescribed restricted-use antimicrobials were from the broad-spectrum penicillin group. Conclusions: Safety in pharmacotherapy may be decisive in the clinical outcome of renal patients, so the multiprofessional contribution plays an important role in maintaining a favorable clinical condition.